Pseudomonas mangrovi sp. nov., isolated from mangrove soil. Issue 2 (2nd January 2019) - Ye, Yanghui; Chen, Can; Ren, Yanhu; Wang, Ruijun; Zhang, Chongya; Han, Shuaibo; Ju, Zhao; Zhao, Zhu; Sun, Cong; Wu, Min
Abstract : A Gram-stain-negative, aerobic, non-motile, short-rod-shaped bacterium, designated as strain TC11 T, was isolated from rhizosphere soil of mangrove forest ( Kandeliaobovata ) in Fugong village, Zhangzhou, Fujian, China. Strain TC11 T grew at 15–45 °C (optimum, 35 °C), 0–8 % (w/v) NaCl (optimum, 1 %, w/v) and pH 5.5–9.5 (optimum, pH 7.5). Phylogenetic analyses revealed that strain TC11 T belonged to a clade of the genus Pseudomonas and showed the highest sequence similarity of 98.4 % to Pseudomonas fluvialis ASS-1 T, followed by Pseudomonas oleovorans subsp. oleovorans DSM 1045 T (97.9 %), Pseudomonas indoloxydans JCM 14246 T (97.7 %), Pseudomonas guguanensis JCM 18416 T (97.6 %) and Pseudomonas alcaliphila JCM 10630 T (97.5 %) on the basis of their 16S rRNA gene sequences. The DNA G+C content was 64.3 mol%. In silico DNA–DNA hybridization and average nucleotide identity values between strain TC11 T and the reference strains were 19–22 % and 72–78 %, respectively. Studies based on the three housekeeping genes, rpoB, gyrB and rpoD, further confirmed that strain TC11 T is a novel member of the genus Pseudomonas . The major fatty acids of strain TC11 T were C16 : 0, summed feature 8 (C18 : 1 ω6c/C18 : 1 ω7 c ) and summed feature 3 (C16 : 1 ω7c/C16 : 1 ω6 c ). The sole isoprenoid quinone was Q-9. The major polar lipids were phosphatidylethanolamine, phosphatidylglycerol and diphosphatidylglycerol. Based on the phenotypic, chemotaxonomic and phylogenetic properties, strain TC11 T represents a novel species of the genus Pseudomonas, for which the name Pseudomonas mangrovi sp. nov., is proposed. The type strain is TC11 T (=KCTC 62159=MCCC 1K03499).